Value of flow cytometry for MRD-based relapse prediction in B-cell precursor ALL in a multicenter setting - S. Modvig; H. Hallböök; H. O. Madsen; S. Siitonen; S. Rosthøj; A. Tierens; V. Juvonen; L. T. N. Osnes; H. Vålerhaugen; M. Hultdin; R. Matuzeviciene; M. Stoskus; et al. (SPRINGERNATURE, 2025)
PCR of TCR/Ig gene rearrangements is considered the method of choice for minimal residual disease (MRD) quantification in BCP-ALL, but flow cytometry analysis of leukemia-associated immunophenotypes (FCM-MRD) is faster and biologically more informative. FCM-MRD performed in 18 laboratories across seven countries was used for risk stratification of 1487 patients with BCP-ALL enrolled in the NOPHO ALL2008 protocol. When no informative FCM-marker was available, risk stratification was based on real-time quantitative PCR. An informative FCM-marker was found in 96.2% and only two patients (0.14%) had non-informative FCM and non-informative PCR-markers. The overall 5-year event-free survival was 86.1% with a cumulative incidence of relapse (CIR5y) of 9.5%. FCM-MRD levels on days 15 (HzR 4.0, p < 0.0001), 29 (HzR 2.7, p < 0.0001), and 79 (HzR 3.5, p < 0.0001) associated with hazard of relapse adjusted for age, cytogenetics, and WBC. The early (day 15) response associated with CIR5y adjusted for day 29 FCM-MRD, with higher levels in adults (median 2.4 x 10(-2) versus 5.2 x 10(-3), p < 0.0001). Undetectable FCM- and/or PCR-MRD on day 29 identified patients with a very good outcome (CIR5y = 3.2%). For patients who did not undergo transplantation, day 79 FCM-MRD > 10(-4) associated with a CIR5y = 22.1%. In conclusion, FCM-MRD performed in a multicenter setting is a clinically useful method for MRD-based treatment stratification in BCP-ALL.